The Relationship of Microplastic Abundance, Flow Rate Discharge and Drainage Profile in Bandar Lampung City, Lampung Province, Indonesia - Alam, ‪Firdha Cahya; Fajar, Mutiara; Patricia, Ester; Novelila, Alisha; Mawaddah, Nurul; Sari, Novi Kartika (Faculty of Geography, Universitas Gadjah Mada, 2024)
The research on microplastics in urban drainage is becoming a concern. In the drainage of Bandar Lampung city, four different anthropogenic activities were investigated: road runoff, industrial activity, public place, and housing area. This study investigated the abundance, characteristics and distribution of microplastics (MPs) through drainage systems in dry weather. A total of sixteen drainage water samples were collected using grab sampling with a horizontal water sampler. Under microscope observation combined with a needle test, the average abundance of MPs was found 3.97±3.4 particles/L, with fibers as the dominant type of MPs. The order of MPs' abundance was industrial area > public area > transportation area > housing area. However, this number of MPs tends to be lower compared to other reported studies. The size of MPs mostly ranged from 500 - 1500 µm (36%). The color of MPs was amply diverse, with blue being in the dominant proportion (43%). Other studies also reported similar findings regarding the type and size range. Through Raman spectroscopy, the identification of polymer types indicated the presence of polyethylene terephthalate. From the correlation analysis, it was found that there was a positive correlation between the abundance of MPs and flow rate discharge, though with a low relationship (r=0.46). This result can be influenced by several factors such as the effects of multiple land use types and pollution sources. The significance of this research lies in its contribution to understanding the extent of microplastic pollution and its potential environmental impact on the Lampung water body.